2003
DOI: 10.4067/s0717-66432003000100004
|View full text |Cite
|
Sign up to set email alerts
|

Forms and Availability of Soil Phosphorus in Temperate Forests in Southern Chile and Flanders

Abstract: This study investigated the different forms and availability of P in soil profiles from temperate forests in southern Chile (two sites: Nothofagus obliqua (Mirb.) Bl. and Nothofagus betuloides (Mirb.) Oerst.) and Flanders, Belgium (two sites: Pinus nigra Arnold and Betula pendula Roth). Soils were sampled according to genetic horizonation and analysed for organic matter, oxalateextractable P, Al and Fe, total inorganic P and total organic P. Phosphorus availability was assessed using an isotopic exchange techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…This may be attributed to lower phosphorus content in the subsurface as well as presence of more organic matter in the surface as compared to subsurface soil. Organic matter on decomposition releases organic molecules, which form complexes with Fe and Al ions thereby blocking the sites which are mainly responsible for fixation of phosphorus [9][10][11]. This is supported by results of another experiment [12] conducted in the same site which showed that addition of organic manure markedly increased the availability of phosphorus in the soil.…”
Section: Resultsmentioning
confidence: 91%
“…This may be attributed to lower phosphorus content in the subsurface as well as presence of more organic matter in the surface as compared to subsurface soil. Organic matter on decomposition releases organic molecules, which form complexes with Fe and Al ions thereby blocking the sites which are mainly responsible for fixation of phosphorus [9][10][11]. This is supported by results of another experiment [12] conducted in the same site which showed that addition of organic manure markedly increased the availability of phosphorus in the soil.…”
Section: Resultsmentioning
confidence: 91%
“…Organic molecules released on decomposition of organic matter form complexes with Fe and Al in the soil thereby blocking the sites which are mainly responsible for fixation of phosphorus in the soil (Juo and Fox, 1977;Subramanian and Kumaraswamy, 1989;Brouwere et al, 2003;Ghosal et al, 2011). Banik et al (2006) also showed that addition of organic manure markedly increased the availability of phosphorus in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in this study moderate labile P represented, on average, 64% of total P o whereas no labile P averaged 31% of total P o . Temperate Chilean forest soils have high contents of organic P (Thomas et al, 1999;De Brouwere et al, 2003), with most of this P present as moderate labile fraction like those forest Andisols reported by Binkley et al (2000) and Spears et al (2001).…”
Section: Tablementioning
confidence: 92%